A trade-off: Antimicrobial resistance and COVID-19 - Johnson, Tess (Bioethics, 2021)
As we combat the COVID-19 pandemic, both the prescription of antimicrobials and the use of biocidal agents have increased in many countries. Although these measures can be expected to benefit existing people by, to some extent, mitigating the pandemic's effects, they may threaten long-term well-being of existing and future people, where they contribute to the problem of antimicrobial resistance (AMR). A trade-off dilemma thus presents itself: combat COVID-19 using these measures, or stop using them in order to protect against AMR. Currently, I argue, we are choosing to continue with these measures, and thus to prioritize combatting COVID-19, without adequate ethical reflection on the AMR-associated costs of these measures. I discuss the magnitude of the possible costs and benefits involved in making the trade-off in favour of COVID-19, and their distribution. I highlight two salient aspects of distribution that can help determine whether combatting COVID-19 whilst exacerbating AMR produces justly distributed costs and benefits: distribution between current and future populations, and distribution between existing geographical populations. Adopting this account, I argue that based on the magnitude and distribution of costs and benefits of combatting COVID-19, we have good reason to rethink this trade-off, and instead consider prioritizing protecting current and future people against AMR, but jettisoning measures against COVID-19 that also exacerbate AMR.